PENGARUH LAYANAN INFORMASI TERHADAP PENINGKATAN BELAJAR EFEKTIF SISWA KELAS X SMK FARMASI IKASARI PEKANBARU TAHUN PELAJARAN 2014/2015 - Iswanto, Budi Iswanto; Yakub, Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to determine the effect of information services to increase effective learning class X SMK Farmasi Ikasari pekanbaru school year 2014/2015. This research was conducted in SMK Farmasi Ikasari pekanbaru from April 2015 through June 2015. The method used was experimental method to pattern one-group pretest-posttest. 1,3,5 class X student population is having problems belejar effective and 117 of the population used as research subjects (saturated sample) data collection instrument used was a questionnaire using Likert scale. Data analysis technique used is the statistical correlation techniques. The result showed that the effect on the improvement of information services effective learning class X SMK Farmasi Ikasari Pekanbaru school year 2014/2015. This is based on the results of analyzes, calculations show thitung> ttable (-9.40> 1.960). So it can be concluded that the effect on the improvement of information services effective learning of students with a contribution of 48% while 52% are influenced by factors - other factors contained in the students themselves and the environment.Keywords: Effect Of Information Services, Effective Learning